Cataloguing And Collaborating In The Age Of Emerging Technologies - Albert, Geetha (2015)
Lean budgets force organizations in particular the libraries who are cost-centres, to devise strategies that make the very most of the resources available. With the abundance of evolving technological innovations and the variety of information that is becoming available to the customer, competitive pressure will continue to intensify for libraries to constantly improve their systems and processes. Development and use of information technology (IT), in particular the latest online cataloguing tools and techniques, enable library professionals in enhancing their delivery systems.